DTI abnormalities in adults with past history of attention deficit hyperactivity disorder: a tract-based spatial statistics study. (August 2015) - Bode, Michaela K; Lindholm, Päivi; Kiviniemi, Vesa; Moilanen, Irma; Ebeling, Hanna; Veijola, Juha; Miettunen, Jouko; Hurtig, Tuula; Nordström, Tanja; Starck, Tuomo; Remes, Jukka; Tervonen, Osmo; et al.
Background: Diffusion tensor imaging (DTI) is a magnetic resonance imaging (MRI) technique enabling visualization and measurement of white matter tracts. Attention deficit hyperactivity disorder (ADHD) has been studied with DTI earlier with variable results, yet there is little research on remitted ADHD. Purpose: To compare the brain white matter between ADHD drug naïve subjects whose ADHD symptoms have mostly subsided and healthy controls. Material and Methods: Tract-based spatial statistics (TBSS) was used to compare 30 subjects with adolescent ADHD with control subjects at the age of 22–23 years. The study population was derived from a population-based Northern Finland Birth Cohort 1986. Fractional anisotropy (FA), mean diffusivity (MD), and measures of diffusion direction (λ1–3 ) were calculated. Permutation testing was used to test for differences in mean values of FA, MD, and λ1–3 between the groups. The results were corrected for multiple comparisons across the whole white matter skeleton. Results: The ADHD group showed increased FA related to decreased radial diffusivity in the left forceps minor ( P  < 0.05). In the vicinity along the same tract, axial diffusion was significantly decreased without any significant effect on FA. No between-group difference in MD was observed. Regressor analysis revealed no gender-, IQ- or GAF-related changes. After removal of left handed subjects the statistical significance was only barely lost. Conclusion: In a setting with remitted ADHD, the results may represent a compensatory mechanism in the left forceps minor.